Phase Transformations During High-Speed Heat Treatment of the System "Carbide (M23C6)/([alpha]-Fe) Matrix"; AIP Conference Proceedings; Vol. 1899 : Prospects of Fundamental Sciences Development (PFSD-2017) - Ivanov Yu. F. Yuriy Fedorovich; Klopotov A. Anatolii; Petrikova E. Elizaveta; Vlasov Yu. Yurii; Kondratyuk А. А. Alexey Alekseevich (Modification of materials structure and properties, 2017)
Title screen